Assessment of animal diversity in Pulau Tinggi, Mersing, Johor for conservation and indicator for potential wildlife tourism - Ng, Yin Hui (2020)
Pulau Tinggi is a marine park that is located in Mersing, Johor. This study aimed to document the checklist of wildlife in Pulau Tinggi and investigate suitable wildlife organisms to be emulated as wildlife tourism products, wildlife tourism hotspots and new wildlife tourism package. Wildlife sampling was conducted in three nature trails in Pulau Tinggi. Different methods were applied to different animal groups. Drift fence pitfall traps and visual encountered surveys were used in the herpetofauna survey. Mist nets were used in bats, while cage traps and camera traps were used for other mammals on the island. Pitfall traps, light traps, and hand catching methods were used for insects. Wildlife sampling were conducted from February 2019 to October 2019. This study successfully documented nine species of amphibians, of which six were newly recorded species in Pulau Tinggi. For the reptile checklist, seven among the fourteen species documented were a new record for Pulau Tinggi. For mammals, twelve species of bats and one species each for large and small mammals. Among all wildlife, insects were the most diverse group which amassed a total of two hundred twenty species. Wildlife tourism was assesed in three nature trails according to each developed tourism packages based on seven criterial of good nature tourism product. From the diversity data gathered, the potential hotspot were determined in three nature trails for each wildlife species. For herpetofauna tourism, Draco melanopogon and Kaloula pulchra were selected as potential tourism products; for bat-based tourism is Pteropus hypomelanus; in camera trap, targeted species for wildlife tourism is Caloenas nicobarica and for entomotourism, lepidoptera order was selected to be developed as a tourism product. The result demonstrated that Trail 3 has a high potential for wildlife tourism since all targeted species were frequently distributed in this trail.